2021
DOI: 10.14423/smj.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Associated Diffuse Large B Cell Lymphoma Found on Revision Arthroplasty of the Knee

Abstract: Fibrin-associated diffuse large B cell lymphoma (FA-DLBCL) is a rare Epstein-Barr viruspositive B cell lymphoma that is nonmassforming, does not directly produce symptoms, and is incidentally discovered on histological examination of tissues excised for other reasons. Despite overlap in morphologic and immunophenotypic features with aggressive B cell neoplasms, FA-DLBCL shows an excellent clinical outcome, even with surgical excision alone. We report an extremely rare occurrence of FA-DLBCL found in associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Ho et al (7) summarized 87 patients with FA-DLBCL. Their literature review revealed that patients with FA-DLBCL had many types of underlying medical conditions, such as cardiac myxoma, thrombus, hematoma, aneurysms, prosthetic valves, breast implants, and cystic lesions at various locations (8)(9)(10)(11)(12). The mechanism of FA-DLBCL development in these lesions remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al (7) summarized 87 patients with FA-DLBCL. Their literature review revealed that patients with FA-DLBCL had many types of underlying medical conditions, such as cardiac myxoma, thrombus, hematoma, aneurysms, prosthetic valves, breast implants, and cystic lesions at various locations (8)(9)(10)(11)(12). The mechanism of FA-DLBCL development in these lesions remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Only seven cases of malignant lymphomas complicating total knee replacement arthroplasty have been reported in the medical literature [1][2][3][4][5][6][7]. The mean time between implantation of the prostheses and lymphoma diagnosis was 7 years (range, 6 months to 16 years).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up was reported in six patients, all of them being free of disease for 8 months to 3 years. In particular, one patient was alive for 2 years without evidence of disease, even though no additional treatment was received other than revision arthroplasty [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FA-LBCL is now recognized as a distinct EBV-driven neoplasm by the 5th edition of WHO classification of hematolymphoid tumors. 2 It is rare, and approximately 60 patients have been reported in English literature until 2022, 3,4,7,9,10,25-31 most frequently associated with cardiac myxomas, with 18 tumors identified. A total of 14 tumors has been identified in association with prosthetic devices and associated thrombi (like cardiac valves and vascular grafts), and knee metallic implants.…”
Section: Discussionmentioning
confidence: 99%